(3cJGH GdENhGfjGJs
(3ChdgG (B:s
(3ehdGi Yde ai GdcQe Jba Ydjg ai GdeWGeQ s
(3BNQgG (B:s
(3CeG UhQI GdZVH abO HQOJ hUhQI GdZjX abO NeOJ BNQ cJGH GdENhGfjGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3LRA efg hgh CHhGH GdESJeGMGJ hGdTaGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs